THE ROLE OF ASTROCYTES IN THE HOMEOSTASIS MAINTAINING IN THE NERVE TISSUE - Silkina, Yu.V.; Khudyakov, A.E.; Klopotsky, G.A.; Khmel, S.I. (World of Medicine and Biology, 2018)
One of the important functions of astrocytes is regulation of the potassium ions concentration in the extracellular fluid. Plasma membrane of astrocytes has a high permeability for potassium and absorbs the potassium excess for the maintain homeostasis of brain tissue. The function of "adsorbents" of potassium astrocytes is due to the presence of special potassium channels of internal rectification - Kir (K-inward rectifier channel), which can transport K + ions only in the cell and allows stabilizing the membrane potential in the hyperpolarization. The most studied is the weakly rectifying channel Kir4.1, the permeability of which slightly changes during membrane depolarization. It has been demonstrated that growth in the astrocytes endfeet cytoplasm of Ca2 + concentration through the activation of glutamate receptors (mGluR) leads to leakage of K + from the endfeet, thereby increasing its concentration in the extracellular fluid. In turn, this activates Ca-channels on vessels’s the smooth muscle cells, increasing the entry of K + into the myocytes, introducing them into hyperpolarization and relaxation. However, the theory about dependence of vasodilation from leakage of K + in the sites of the astrocyte endfeet proved to be inadequate, since data appeared that in Kir4.1-knockout and wild-type mice the K+ extracellular concentration was slightly different after direct stimulation of astrocytes. Changing cerebral blood flow by control of the smooth myocytes tone in the brain vessels is critical to ensuring that the delivery rate of nutrients matches the level of neuronal activity. It is known that switching vasoconstriction and vasodilation occurs by adenosine, oxygen and lactate. The close association of astrocytes with the vessels of the brain has long been recognized, but it is known that astrocytes react to a higher concentration of extracellular glutamate by joining it to mGluR, which increases the concentration of intracellular calcium, etc. (mechanism described above). Interestingly, a high concentration of calcium in astrocytes can cause both vasoconstriction and vasodilation. Another important function of astrocytes is maintaining of the water balance in the brain tissue. It was found that the movement of water to the brain sector occurs at the expense of special channels in the cell membranes - aquaphorines (AQP). The role of AQP4, which is found exclusively in glial cells and is aqueous selective transporter, is widely studied, which is widely represented in the membrane of astrocytral feet in areas of their contact with vessels. Also, thick clumps of AQP4 are found in ependymal cells membranes, which extend the spinal cord and brain ventricles. AQR4 plays a very important regulatory role in pathological conditions of the brain edema. Three mechanisms of edema formation are known: cytotoxic, vasogenic and interstitial mechanisms. However, the strategic role of AQP4 in astrocytes was studied during the oncogeneous vasculogenesis, involves astrocytes that migrate to glial scar. In migratory active astrocytes the AQP4 is densely located in the lamelopody regions and contributes to the increased water movement through the plasma membrane, which facilitates the movement of the cell.